PERANAN STATISTICAL QUALITY CONTROL (SQC) DALAM PENGENDALIAN KUALITAS: STUDI LITERATUR - Syarifah Nazia; Safrizal; Muhammad Fuad (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2023)
This research is a literature study with descriptive qualitative research using literature review which describes the role of Statistical Quality Control in Quality Control. This research uses various sources such as journals, articles, and relevant documents. This literature study focuses on the Role of Statistical Quality Control in Quality Control. Companies really need supervision in each production process, so that companies can know the quality of the products produced. With a quality product, the company will benefit due to increased sales volume and of course it will make consumers feel more satisfied and can avoid complaints from customers after buying or using the product. SQC is a problem-solving tool used in monitoring, analyzing, improving, controlling and managing products in the process of using statistical methods. The SQC method can be used to find errors in the production process that are caused by product defects or damage, so that more action can be taken to overcome problems that cause product damage Key Words: Quality, Control Quality, SQC